TOURIST PREFERENCES OF THE RESIDENTS OF KOSZALIN (Research Bulletins of the Faculty of Economic Sciences, 2021)
The main aim of the research was to determine the tourist preferences of Koszalin residents. The study was conducted with the use of a questionnaire consisting of 15 questions and a record. Data was collected among the inhabitants of Koszalin via the Internet from March to April 2020. 50 people replied to the questionnaire. As a result of the analyzes, the goal was achieved and the assumption that the departure preferences of Koszalin residents vary. According to the conducted analyzes, the tourist preferences of Ko-Shalin's inhabitants are influenced by: tourist values, price, places free from terrorist threats, places with limited occurrence of natural hazards, places different from those where they operate on a daily basis.
Keywords: tourism, tourist trips, departure preferences, Koszalin